Development of a Virtual Laboratory for Bacterial Culture as a Biology Learning Media - Lopiani, Salmanera Senja; Muzakki, Muhammad Naufal; Fahmi, Wahyunisa Maulia; Wardhani, Irma Yuniar; Fikri, Achmad Ali (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2025)
This research aims to develop a virtual laboratory Android application entitled "Bacterial Culture" as an innovative learning media in Microbiology courses. This application simulates the bacterial culture process, including media preparation, sterilization techniques, inoculation, and analysis of results. This research is a Research and Development (R&D) study using the Borg and Gall model which was adapted into six stages. The design validation stage includes validation of media and material experts, namely microbiology lecturers and small group trials involving third semester Biology Education students at IAIN Kudus. The results of expert validation by microbiology course lecturers show that this media obtained a validity score of 91.6% (very valid), and practicality testing by 3rd semester students obtained a score of 61.6% (Special). These findings indicate that the virtual laboratory "Bacterial Culture" is a learning medium that can support students' understanding of bacterial culture practicum before carrying out practicum in the laboratory. This study contributes to the progress of technology-based education which is aligned with the Independent Campus Learning Curriculum (MBKM).